An in situ energy-dispersive X-ray diffraction study of the hydrothermal crystallizations of open-framework gallium oxyfluorophosphates with the ULM-3 and ULM-4 structures - Walton, R; Loiseau, T; O'Hare, D; Ferey, G (1999)
The hydrothermal crystallizations of open-framework gallium oxyfluorophosphates with the ULM-3 and ULM-4 structures have been studied in situ using energy-dispersive X-ray diffraction. Data collected during reactions in a large volume (∼25 mL) cell under real laboratory conditions have allowed the growth of crystalline phosphates from amorphous gel precursors to be observed. A number of amines have been used in the syntheses, and the nature of the phosphorus source has been investigated. Kinetic data have been determined by monitoring changes in the integrated intensities of Bragg reflections and modeled using the Avrami - Eroféev expression. The results suggest that the reactions are diffusion controlled; Avrami exponents of ∼0.5 are found, and the rate of crystallization is not affected by temperature (140-200°C). Subsequent modeling using the Jander expression confirms the diffusion-controlled nature of reaction. When P2O5 is used instead of the usual H3PO4 in the synthesis of gallium ULM-3 with 1,3-diaminopropane, a previously unknown crystalline phase is observed to form before the onset of crystallization of the product. This phase is transient and its growth and decay have a marked affect on the growth curve of the ULM-3. Attempts to recover the new phase by quenching the hydrothermal processes revealed that the intermediate gallium phase converts to a different phase on cooling, and this second novel compound was subsequently prepared at room temperature. Analytical electron microscopy shows the new material to be a gallium phosphate with Ga:P ratio of 1:2. © 1999 American Chemical Society.